Priorities evaluation of cyber defense mechanisms of national utilities payment system through the use of the analytic hierarchy process - Стремецька, Мирослава Станіславівна (Ukrainian Information Security Research Journal, 2019)
The article is devoted to the problem of evaluation of the influence of cyber defense mechanisms on the reaching security of national utilities payment system. With growing demand for the development of communication systems aimed at satisfying public needs, implementing e-government services, e-commerce and electronic document management there is an urgent need to construct organizational and technical cybersecurity models as a complex of measures, forces and means for their cyber defense. It was important that the proposed approach to the development of such models was not only one-size-fits-all to all objects of cyber defense and, most crucially, took into account very specific features of each individual system functioning. The Security Management System (SeMS) hierarchical model of national utilities payment system that included both the technological features of the individual subsystems and the guidelines for interaction between them in terms of the main objective - to achieve a safety state of the system, in general, was designed. The priorities evaluation of cyber defense mechanisms through the use of The Analytic Hierarchy Process (AHP) was performed based on the designed model. The results of evaluation showed that the first and foremost attention should be focused on e-mail and web security (29,9%), while computer network security (25,6%) got the second place, mobile security (19,53%) the third place, cyber defense mechanisms for endpoint protection (12,25%) the fourth place, data centers security (7,99%) the fifth place and cloud security (4,73%) the last place respectively. The methodology allows to implement a system approach to the construction of organizational and technical models of complex hierarchical systems; makes it possible to obtain quantitative scores of the decisions priorities, based on which it is possible to formalize the procedure of choosing the various scenarios for the work of the SeMS; helps to develop the appropriate mathematical apparatus for the study on number of other complex objects of cyber defense within the national cyber security system of Ukraine.